A universal strategy for the construction of polymer brush hybrid non-glutaraldehyde heart valves with robust anti-biological contamination performance and improved endothelialization potential. (1st April 2023) - Yu, Tao; Zheng, Cheng; Chen, Xiaotong; Pu, Hongxia; Li, Gaocan; Jiang, Qing; Wang, Yunbing; Guo, Yingqiang
Abstract: With the intensification of the aging population and the development of transcatheter heart valve replacement technology (THVR), clinical demand for bioprosthetic valves is increasing rapidly. However, commercial bioprosthetic heart valves (BHVs), mainly manufactured from glutaraldehyde cross-linked porcine or bovine pericardium, generally undergo degeneration within 10-15 years due to calcification, thrombosis and poor biocompatibility, which are closely related to glutaraldehyde cross-linking. In addition, endocarditis caused by post-implantation bacterial infection also accelerates the failure of BHVs. Herein, a functional cross-linking agent bromo bicyclic-oxazolidine (OX-Br) has been designed and synthesized to crosslink BHVs and construct a bio-functionalization scaffold for subsequent in-situ atom transfer radical polymerization (ATRP). The porcine pericardium cross-linked by OX-Br (OX-PP) exhibits better biocompatibility and anti-calcification property than the glutaraldehyde-treated porcine pericardium (Glut-PP) as well as comparable physical and structural stability to Glut-PP. Furthermore, the resistance to biological contamination especially bacterial infection of OX-PP along with anti-thrombus and endothelialization need to be enhanced to reduce the risk of implantation failure due to infection. Therefore, amphiphilic polymer brush is grafted to OX-PP through in-situ ATRP polymerization to prepare polymer brush hybrid BHV material SA@OX-PP. SA@OX-PP has been demonstrated to significantly resist biological contamination including plasma proteins, bacteria, platelets, thrombus and calcium, and facilitate the proliferation of endothelial cells, resulting in reduced risk of thrombosis, calcification and endocarditis. Altogether, the proposed crosslinking and functionalization strategy synergistically achieves the improvement of stability, endothelialization potential, anti-calcification and anti-biofouling performances for BHVs, which would resist the degeneration and prolong the lifespan of BHVs. The facile and practical strategy has great potential for clinical application in fabricating functional polymer hybrid BHVs or other tissue-based cardiac biomaterials. Statement of significance: Bioprosthetic heart valves (BHVs) are widely used in valve replacements for severe heart valve disease, and clinical demand is increasing year over year. Unfortunately, the commercial BHVs, mainly cross-linked by glutaraldehyde, can serve for only 10–15 years because of calcification, thrombus, biological contamination, and difficulties in endothelialization. Many studies have been conducted to explore non-glutaraldehyde crosslinkers, but few can meet high requirements in all aspects. A new crosslinker, OX-Br, has been developed for BHVs. It can not only crosslink BHVs but also serve as a reactive site for in-situ ATRP polymerization and construct a bio-functionalization platform for subsequent modification. The proposed crosslinking and functionalization strategy synergistically achieves the high requirements for stability, biocompability, endothelialization, anti-calcification, and anti-biofouling propeties of BHVs. Graphical Abstract: Image, graphical abstract